Análise do desempenho econômico-financeiro de hospitais com a utilização de índices-padrão: um estudo nos hospitais privados de Florianópolis - Lira, Clarisse Andrade de (2017)
The present dissertation aims to analyze the economic-financial performance of private hospitals in Florianópolis through standard indexes from 2013 to 2015. The model proposed by Matarazzo (2010) was used to construct a standard index to compare the Performance of the private hospital sector. From there, to calculate the same indexes of the main private hospitals of Florianópolis in order to compare the performance of these with the performance of the sector. In the first phase of the research, the quantitative phase, the research strategy adopted was the bibliographic research, based on secondary data - the financial statements of hospital institutions. From this, a statistical analysis was performed for calculations and tabulations of the standard indexes. In the second phase of the research, which involves qualitative data, semi-structured interviews were conducted with hospital managers in Florianópolis in order to generate validation of data from the first phase. Regarding the analysis and treatment of data, the main results found indicate, for the great majority of the indices, a wide difference between the standard indices of the private hospital sector and the indicators of the hospitals of Florianópolis. When measuring a global score for the performance of hospitals in Florianópolis in 2015, this classification was considered Deficient. The scenario pointed out in the research reveals a critical economic-financial scenario, capable of compromising the sustainability of the Florianópolis private hospital sector.